2017
DOI: 10.1128/aac.02529-16
|View full text |Cite
|
Sign up to set email alerts
|

WCK 5107 (Zidebactam) and WCK 5153 Are Novel Inhibitors of PBP2 Showing Potent “β-Lactam Enhancer” Activity against Pseudomonas aeruginosa, Including Multidrug-Resistant Metallo-β-Lactamase-Producing High-Risk Clones

Abstract: Zidebactam and WCK 5153 are novel ␤-lactam enhancers that are bicyclo-acyl hydrazides (BCH), derivatives of the diazabicyclooctane (DBO) scaffold, targeted for the treatment of serious infections caused by highly drug-resistant Gram-negative pathogens. In this study, we determined the penicillin-binding protein (PBP) inhibition profiles and the antimicrobial activities of zidebactam and WCK 5153 against Pseudomonas aeruginosa, including multidrug-resistant (MDR) metallo-␤-lactamase (MBL)-producing high-risk cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
113
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 50 publications
7
113
1
1
Order By: Relevance
“…Since BLEs were antibacterially inactive against the strains studied and also were noninhibitors of MBLs, the lowering of the MICs of PBP3 binding agents cefepime and aztreonam in combination with BLEs appears to be an outcome of inactivation of complementary PBPs, resulting in growth inhibition. In the past, PBP binding data of BLEs were published for E. coli, A. baumannii, and P. aeruginosa (14,15), while in the present study, for the first time, we demonstrate high-affinity binding to K. pneumoniae PBP2. The time-kill studies showed that both zidebactam and WCK 5153 enhanced the bactericidal activity of cefepime and aztreonam.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Since BLEs were antibacterially inactive against the strains studied and also were noninhibitors of MBLs, the lowering of the MICs of PBP3 binding agents cefepime and aztreonam in combination with BLEs appears to be an outcome of inactivation of complementary PBPs, resulting in growth inhibition. In the past, PBP binding data of BLEs were published for E. coli, A. baumannii, and P. aeruginosa (14,15), while in the present study, for the first time, we demonstrate high-affinity binding to K. pneumoniae PBP2. The time-kill studies showed that both zidebactam and WCK 5153 enhanced the bactericidal activity of cefepime and aztreonam.…”
Section: Discussionsupporting
confidence: 68%
“…Cefepime MICs were higher for all of the strains. Zidebactam and WCK 5153 do not possess ␤-lactamase-inhibitory activity against MBL enzymes (15). In the present study, neither BLE showed significant antibacterial activity against the K. pneumoniae strains tested.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations